Histopathology of Seminiferous Tubules of Wistar Rats (Rattus norvegicus) Exposed to Electric Mosquito Repellent with Active Ingredient D-Allethrin - Salwa Nabila Izzati; Desy Armalina; RR. Mahayu Dewi Ariani; Fanti Saktini (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2021)
Background: An increase in mosquito-borne diseases has resulted in the use of mosquito repellents, especially electric ones in Indonesia. One of the active ingredients of electric mosquito repellent, namely d-allethrin, cangenerate free radicals resulting in oxidative stress. Oxidative stress on the testes can interfere with the spermatogenesis stage in the seminiferous tubules.Objective: Determine the histopathology of seminiferous tubules of Wistar rats exposed to electric mosquito repellents with the active ingredient d-allethrin.Methods: This study used a true experimental design with a post test only control group design. A sample of 25 Wistar rats was divided into 5 groups. The control group (K) was given only standard feed. Treatment group 1 (P1), treatment group 2 (P2), treatment group 3 (P3), and treatment group 4 (P4) were exposed to electric mosquito repellents with active ingredient d-allethrin sequentially for 8 hours/day, 12 hours/day, 18 hours/day, and 24 hours/day. After 30 days the rats were terminated. The testes were taken for histopathological observation with HE staining and assessed according to the Johnsen score criteria.Results: Based on the score, the mean value of the control group was 9.4, P1: 8.36, P2: namely 7.68, P3: 5.84, and P4: 5.64.The results of statistical tests using the one way Anova showed a significant difference (p <0.001).Conclusion: Exposure to electric mosquito repellent containing the active ingredient d-allethrin caused differences in the histopathology of seminiferous tubules score of Wistar rats.